Consensus on pre-commissioning stages for cogeneration and combined cycle power plants - Light, Roger W. (John Wiley & Sons Ltd, 2017)
Prepared by Combined Cycle Task Group For the Water Technology Subcommittee of the ASME Research and Technology Committee On Water and Steam in Thermal Systems. This publication is an important adjunct to several previously published documents prepared to inform, educate and assist the reader in adequately considering and planning for the many major activities involved in the design, construction and start-up of cogeneration and combined cycle power plants. Experience has shown that failure to consider the complex interrelationships between the various component systems can result in costly delays in project completion and turn over dates. Additionally, incorrect procedures and planning can result in damage or failure of key pieces of equipment or systems during subsequent operation.